2019
DOI: 10.3390/rs11192223
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of AOD Correction and Spatial Scale on the Correlation between High-Resolution AOD from Gaofen-1 Satellite and In Situ PM2.5 Measurements in Shenzhen City, China

Abstract: Satellite-derived aerosol optical depth (AOD) is widely used to estimate surface PM2.5 concentrations. Most AOD products have relatively low spatial resolutions (i.e., ≥1 km). Consequently, insufficient research exists on the relationship between high-resolution (i.e., <1 km) AOD and PM2.5 concentrations. Taking Shenzhen City, China as the study area, we derived AOD at the 16-m spatial resolution for the period 2015–2017 based on Gaofen-1 (GF-1) satellite images and the Dark Target (DT) algorithm. Then, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Compared with the remarkable influence of sampling frequency, the difference in spatial resolution mainly impacts the consistence of MODIS PM 2.5 results in detailed scales (Figure 7), which is important for exposure assessment on a regional scale such as the BTH. Most previous studies focus on influence of spatial resolution on AOD-PM 2.5 relationship [23][24][25][26]. It is found that correlation of AOD-PM 2.5 gets slightly higher for high-resolution PM 2.5 estimation in the megacity of Beijing in northern China [31], but is not obvious on a regional scale (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Compared with the remarkable influence of sampling frequency, the difference in spatial resolution mainly impacts the consistence of MODIS PM 2.5 results in detailed scales (Figure 7), which is important for exposure assessment on a regional scale such as the BTH. Most previous studies focus on influence of spatial resolution on AOD-PM 2.5 relationship [23][24][25][26]. It is found that correlation of AOD-PM 2.5 gets slightly higher for high-resolution PM 2.5 estimation in the megacity of Beijing in northern China [31], but is not obvious on a regional scale (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, whether satellite PM 2.5 can capture the temporal variations and actual magnitude of PM 2.5 in northern China can be obviously be impacted by the sampling frequency of satellite AOD. However, previous studies mainly focused on the influence of satellite AOD parameters such as spatial resolution on modeling of the AOD-PM 2.5 relationship [23][24][25][26]. Even the several widely used MODIS aerosol products have remarkable differences in sampling frequency and spatial resolution [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, after applying vertical and humidity corrections of AOD following previous works [57,58], the spatial resolution effect on the AOD-PM 2.5 correlation still holds (not shown). Note that the spatial resolution range may affect the sensitivity of AOD-PM 2.5 correlation on resolution.…”
Section: Discussionmentioning
confidence: 67%
“…Note that the spatial resolution range may affect the sensitivity of AOD-PM 2.5 correlation on resolution. For instance, Wu et al [57] found that, as degrading spatial resolution, the correlation in Shenzhen City in summer rapidly increases until reaching the peak at about 1 km resolution and then slowly decreases when going to coarser resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…MODIS has been widely used for the AOD estimation over land and ocean since early 2000 [ 16 , 17 , 19 22 ]. Variation of AOD over India has also been extensively studied using MODIS aerosol data [ 18 , 23 25 ]. Moreover, all the above-mentioned research works have been conducted under the usual natural conditions without any restrictions on anthropogenic activities.…”
Section: Introductionmentioning
confidence: 99%